2011
DOI: 10.1037/a0025286
|View full text |Cite
|
Sign up to set email alerts
|

Risk and resilience in military families experiencing deployment: The role of the family attachment network.

Abstract: Deployment separation constitutes a significant stressor for U.S. military men and women and their families. Many military personnel return home struggling with physical and/or psychological injuries that challenge their ability to reintegrate and contribute to marital problems, family dysfunction, and emotional or behavioral disturbance in spouses and children. Yet research examining the psychological health and functioning of military families is scarce and rarely driven by developmental theory. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
185
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(209 citation statements)
references
References 76 publications
9
185
2
13
Order By: Relevance
“…It contributes to the family-related trauma research by showing the importance of a whole family approach that includes parents, children, siblings, and societal context (Riggs & Riggs, 2011). It would be fruitful to further analyse the perceptions, experiences, and mental health of mothers, fathers, and multiple siblings living in war areas in order to further develop the body of family systems-informed trauma research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It contributes to the family-related trauma research by showing the importance of a whole family approach that includes parents, children, siblings, and societal context (Riggs & Riggs, 2011). It would be fruitful to further analyse the perceptions, experiences, and mental health of mothers, fathers, and multiple siblings living in war areas in order to further develop the body of family systems-informed trauma research.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found complex dynamics in attachment relations and identified several ways that family members show vulnerability and resilience in the face of traumatic events (Besser & Neria, 2010; Freedman, Gilad, Ankri, Roziner, & Shalev, 2015). A family’s atmosphere, values, beliefs, relational scripts, codes, histories, and emotional sharing all influence family members’ responses to trauma (Riggs & Riggs, 2011; Walsh, 2007). Family systems theories provide insight into family members’ dynamic social and mental health responses to stress, including compensatory, buffering, and additive dynamics (Davies & Cicchetti, 2004; Minuchin, 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson et al (2011) report in their investigation of U.S. Army soldiers that 82% were satisfied or very satisfied with their marriages. Riggs and Riggs' (2011) theoretical study investigating resilience in military families in terms of a family attachment network model states that over the last 10 years most veterans and families in the United States have demonstrated a positive adaptation during and after operational deployment. Sheppard et al (2010) report in their literature review that a wealth of literature supports the idea that military families are generally resilient.…”
Section: Discussionmentioning
confidence: 99%
“…There is also limited information about the factors that differentiate those families who do well from those who do not. In this area, too, there are conceptual models that need to be tested (Adler, Zamorski, & Britt, 2011;S. Riggs & D. Riggs, 2011).…”
Section: Gaps In Reintegration Researchmentioning
confidence: 99%